WACANA FIKSIMINI BAHASA INDONESIA: ANALISIS STRUKTUR, KETERPADUAN, PERMAINAN BAHASA, DAN FUNGSI - Cicik Tri Jayanti (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2016)
This study is aimed to describe the characteristics of mini fiction by explaining the structure and coherence between elements, forms of language, and discourse functions in Indonesian mini fiction. It is a qualitative study by using mini fiction discouse as research objects. The research data were in the form of tweets by the users who retweeted any tweets from @fiksimini account. Thus, the data collected in the research were written and collected by transcribing the data. The results of the study showed that (1) the structure of mini fiction discourse consists of three elements, topic, title and content; (2) the language play in the discourse was presented through the reader’s understanding of the texts and some distortion of the language varieties; and (3) the mini fiction discourse has four functions, such as emotive, retorical, cognitive and poetic speech function.   Permalink/DOI: dx.doi.org/10.17977/um015v44i22016p175